Evaluation of feed restriction effects on mineral metabolism of intact male, female and castrated male goat kids - Santos, Paula Fernanda Varella [UNESP] (2019)
The objective of the present study was to evaluate the effects of feed restriction on calcium (Ca), phosphorus (P) and magnesium metabolism in goat kids from 15 to 30 kg bodyweight, and to evaluate the role of sex in these processes. The study used a split plot design comprising three sex groups (intact males, castrated males and females), and the subplot comprised three levels of feed restriction (0% (ad libitum), 25% and 50%). Mineral intake and retention, mineral concentration in the blood, alkaline phosphatase activity and bone mineral density (BMD) of the femur were determined. The data were analysed as mixed models. Daily Ca, P and magnesium retention in the body decreased linearly with increasing feed restriction (P < 0.05). At 50% feed restriction, we observed a 22% reduction of alkaline phosphatase activity, and 9% and 7% reductions of Ca and P contents in blood serum. The BMD of females fed ad libitum was greater than castrated and intact males, whereas when subjected to 50% feed restriction, no differences in BMD were noted among the sexes (P < 0.01). Irrespective of feed restriction, females tended to retain less P in their bodies (P < 0.10) and tended to have the lowest P serum concentrations (P = 0.08). Our results indicated that only females showed decreased BMD under feed restriction Ca, P and magnesium metabolism in prepubertal Saanen goat kids was mainly affected by feed restriction, whereas sex mainly affected the P metabolism.